Jesus was a refugee: unpacking the theological implications - Aspray, B (Wiley, 2023)
This article is an in-depth exploration of the divine purpose for Jesus’ refugeehood (recorded in Matthew 2) and its theological implications. Part One finds three reasons for Jesus’ displacement: (1) to recapitulate the displacement in Israel's story, (2) to recapitulate the exile of Adam and Eve, (3) to point forward to the Church's calling to be ‘aliens and strangers’ in the world. From this basis, Part Two draws two contemporary implications: (1) to transform refugees from ‘other’ to ‘same’ in the eyes of Christian citizens, (2) to reassess the notion of a ‘Christian nation’.